Preparation method of non-phosphorus corrosion and scale inhibitor for highly corrosive water
Through the synergistic effect of the graft copolymer produced by unsaturated monomers and natural polysaccharide polymers and metal corrosion inhibitors, a phosphorus-free corrosion-resisting scale inhibitor is formed, which solves the corrosion and scale problems of strongly corrosive water quality, and reduces phosphorus pollution, achieving the goal of environmental protection and sustainable development.
Patent Information
- Application Number
- CN202411942085.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-02-28
AI Technical Summary
When dealing with highly corrosive water quality, it is difficult to effectively prevent corrosion and scale. At the same time, there is phosphorus pollution problem, which leads to environmental pollution and difficult treatment.
The graft copolymer produced by unsaturated monomers and natural polysaccharide polymers work together with the metal corrosion inhibitor to form a phosphorus-free corrosion-resisting scale inhibitor. The graft copolymer is adsorbed to form a barrier layer on the metal surface to slow down corrosion and reduce the eutrophication of water quality through biodegradation.
It has achieved effective corrosion inhibition and scale inhibition of strongly corroded water quality, reduced metal corrosion and scale formation, avoided phosphorus pollution, and has the characteristics of environmental protection and sustainable development.
Smart Images

Figure BDA0005212757130000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment, and particularly relates to a method for preparing a phosphorus-free corrosion and scale inhibitor for highly corrosive water. Background Art
[0002] 80% of industrial water in my country is circulating cooling water. Saving industrial circulating cooling water is the key to the rational use of water resources. Scientific and technological progress has made people realize that increasing the concentration ratio of circulating cooling water can effectively reduce industrial water use and pollution emissions. The concentration ratio refers to the ratio of the salt content in circulating water to the salt content in supplementary water, and is an important technical and economic indicator for measuring the recycling rate of cooling water. A high concentration ratio means less supplementary water and sewage discharge. Therefore, the use of high concentration ratio circulating cooling water treatment technology is the main method of industrial water saving. Cooling water is constantly used repeatedly in the cycle. Due to various reasons such as increased water temperature, changes in water flow rate, water evaporation, and concentration of various inorganic ions and organic substances, serious sediment adhesion, equipment corrosion, and blockage of pipes caused by the large-scale growth of microorganisms will occur. Therefore, by stabilizing the water quality of circulating cooling water, it is possible to reduce sewage discharge, achieve the purpose of increasing the concentration ratio of circulating cooling water, and save water.
[0003] In the prior art, low-hardness or ultra-low-hardness water is extremely corrosive when used in industrial circulating cooling water, so this type of water is also called highly corrosive water. The treatment method for this type of highly corrosive water is to add a certain amount of calcium and alkali (such as calcium chloride and sodium carbonate) to the industrial circulating cooling water system, artificially increase the hardness and alkalinity of the circulating cooling water, and then use a water treatment agent and process suitable for medium- and high-hardness alkalinity water to treat it. However, this treatment method has the following problems: (1) If too much calcium and alkali are added, the scale inhibition effect of the water treatment agent is poor, which can easily cause scaling of the water system; (2) If too little calcium and alkali are added, the corrosion inhibition effect of the water treatment agent is greatly reduced, which can easily cause corrosion of the water system; (3) The operation is cumbersome and the management is inconvenient, and it cannot ensure the safe, full-load, and long-term operation of the production equipment.
[0004] In order to solve the corrosion and scaling problems of highly corrosive water, Chinese invention patent CN1063803C proposed a composite corrosion inhibitor and scale inhibitor for highly corrosive water. Although the corrosion inhibitor and scale inhibitor adopts a low-phosphorus formula, it still contains phosphorus components. Too high phosphorus content will lead to eutrophication of water bodies and cause environmental damage. Since phosphorus-based agents need to be used in combination with calcium ions, they are not effective in ultra-low hard water and are difficult to handle. In addition, this type of composite corrosion inhibitor and scale inhibitor usually relies on metal salt corrosion inhibitors and is supplemented by phosphorus-based agents, which leads to high costs and serious pollution, while wasting natural resources and is not conducive to sustainable development. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the present invention provides a method for preparing a phosphorus-free corrosion and scale inhibitor for highly corrosive water, which makes the water treatment agent phosphorus-free, safe, green and environmentally friendly without affecting the performance of the water treatment agent.
[0006] The main technical solutions adopted in the present invention are:
[0007] A method for preparing a phosphorus-free corrosion and scale inhibitor for highly corrosive water comprises the following steps:
[0008] S1: In an inert gas environment, natural polysaccharides are mixed with distilled water for gelatinization;
[0009] S2: Cooling the gelatinized system obtained in step S1 to a certain temperature, adding unsaturated monomers, stirring until stable, adding initiator solution, stirring, and performing graft copolymerization reaction;
[0010] S3: After cooling the reaction system of step S2 to room temperature, anhydrous ethanol is added, and the mixture is allowed to stand, filtered, and dried to obtain a grafted crude product;
[0011] S4: using an organic solvent to perform Soxhlet extraction on the grafted crude product to obtain a refined grafted product;
[0012] S5: stirring and dissolving the refined grafted product and the metal corrosion inhibitor aqueous solution, and mixing them evenly.
[0013] Preferably, in S1, the gelatinization temperature is 70-90°C, and the gelatinization time is 20-60 min.
[0014] Preferably, in S1, the natural polysaccharide polymer is one or more of starch and chitosan.
[0015] Preferably, in S2, the gelatinization system is cooled to 40-50°C.
[0016] Preferably, the mass ratio of the natural polysaccharide to the unsaturated monomer is 1:1-1:3.
[0017] Preferably, the added amount of the initiator is 5%-15% of the mass of the unsaturated monomer.
[0018] Preferably, in S2, the unsaturated monomer is one or more of acrylamide, sodium allyl sulfonate, methyl methacrylate, and methyl acrylate.
[0019] Preferably, the initiator is sodium persulfate-sodium bisulfite.
[0020] Preferably, the metal corrosion inhibitor is one or more of zinc salt, gluconic acid, and benzotriazole.
[0021] Beneficial effects: The present invention provides a method for preparing a phosphorus-free corrosion and scale inhibitor for highly corrosive water, which has the following advantages:
[0022] (1) In the present invention, the graft copolymer generated by unsaturated monomers and natural polysaccharide polymers works synergistically with metal corrosion inhibitors to achieve corrosion inhibition, wherein the graft copolymer can be adsorbed on the metal surface and acts as a barrier layer in the metal area covered by the adsorbed particles. The adsorbed particles form a monomolecular layer on the metal surface, inhibiting the cathode reaction and / or the anode reaction during the metal corrosion process, thereby reducing the area of the metal surface where the electrode reaction occurs, thereby slowing down the rate at which the metal is corroded and playing a corrosion inhibition role.
[0023] (2) In the present invention, the graft copolymer formed by the unsaturated monomer and the natural polysaccharide polymer is biodegradable. Since there is no phosphorus pollution, the eutrophication of water quality is reduced, which is beneficial to reduce the growth of bacteria and moss in the circulating water system, thereby reducing the amount of bactericidal algaecides used in the circulating water and reducing the secondary pollution caused by chlorine disinfection;
[0024] (3) The phosphorus-free corrosion and scale inhibitor of the present invention has a production cost similar to that of a phosphorus-containing formulation, and has obvious advantages in replacing phosphorus-based formulations in industrial applications. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.
[0026] Example 1
[0027] In this embodiment 1, a phosphorus-free corrosion and scale inhibitor for highly corrosive water is prepared, and the specific method is as follows:
[0028] 5g starch and 100mL distilled water were added to a four-necked flask containing a condenser, a thermometer, and a stirring device, and inert gas N2 was introduced, and gelatinization was carried out at 80°C for 30min. After gelatinization, the gelatinization system was cooled to 40°C, 5g methyl acrylate and 10g acrylamide were added, and the mixture was stirred for 10min. An aqueous solution containing 1.3g sodium persulfate-sodium bisulfite was slowly added dropwise, and the mixture was stirred for 3h. After the reaction system was cooled to room temperature, 350mL of anhydrous ethanol was added, and a white precipitate was obtained by standing. The grafted crude product was filtered and vacuum dried to obtain a grafted crude product. Subsequently, acetone was used as an organic solvent to perform Soxhlet extraction on the grafted crude product to obtain a refined grafted product. Finally, 10g zinc sulfate heptahydrate, 5g gluconic acid, 1g benzotriazole, and 100g water were added, stirred and dissolved, and the mixture was uniformly mixed to obtain a phosphorus-free corrosion and scale inhibitor.
[0029] Example 2
[0030] In this embodiment 2, a phosphorus-free corrosion and scale inhibitor for highly corrosive water is prepared, and the specific method is as follows:
[0031] 5g chitosan and 100mL distilled water were added to a four-necked flask containing a condenser, a thermometer, and a stirring device, and inert gas N2 was introduced, and gelatinization was carried out at 80°C for 30min. After gelatinization, the gelatinization system was cooled to 40°C, 15g acrylamide was added, and it was stabilized for 10min. A solution containing 1.3g sodium persulfate-sodium bisulfite was slowly added dropwise, and the reaction was stirred for 3h. After the reaction system was cooled to room temperature, 350mL of anhydrous ethanol was added and allowed to stand to obtain a white precipitate. The grafted crude product was filtered and vacuum dried to obtain a grafted crude product. Subsequently, acetone was used as an organic solvent to perform Soxhlet extraction on the grafted crude product to obtain a refined grafted product. Finally, 10g zinc sulfate heptahydrate, 5g gluconic acid, 1g benzotriazole, and 100g water were added to stir and dissolve, and the phosphorus-free corrosion and scale inhibitor was obtained by mixing evenly.
[0032] Example 3
[0033] In this embodiment 3, a phosphorus-free corrosion and scale inhibitor for highly corrosive water is prepared, and the specific method is as follows:
[0034] 8g starch and 100mL distilled water were added to a four-necked flask containing a condenser, a thermometer, and a stirring device, and inert gas N2 was introduced, and gelatinization was carried out at 80°C for 30min. After gelatinization, the gelatinization system was cooled to 50°C, 5g sodium allyl sulfonate and 10g acrylamide were added, and the mixture was stabilized for 10min. A solution containing 1.5g sodium persulfate-sodium bisulfite was slowly added dropwise, and the reaction was stirred for 3h. After the reaction system was cooled to room temperature, 350mL of anhydrous ethanol was added and allowed to stand to obtain a white precipitate, which was filtered and vacuum dried to obtain a grafted crude product. Subsequently, acetone was used as an organic solvent to perform Soxhlet extraction on the grafted crude product to obtain a refined grafted product. Finally, 10g zinc sulfate heptahydrate, 5g gluconic acid, 1g benzotriazole, and 100g water were added, stirred and dissolved, and mixed evenly to obtain a phosphorus-free corrosion and scale inhibitor.
[0035] Example 4
[0036] In this embodiment 4, a phosphorus-free corrosion and scale inhibitor for highly corrosive water is prepared, and the specific method is as follows:
[0037] 8g chitosan and 100mL distilled water were added to a four-necked flask containing a condenser, a thermometer, and a stirring device, and inert gas N2 was introduced, and gelatinization was carried out at 80°C for 30min. After gelatinization, the gelatinization system was cooled to 50°C, 15g acrylamide was added, and it was stabilized for 10min. A solution containing 1.5g sodium persulfate-sodium bisulfite was slowly added dropwise, and the reaction was stirred for 3h. After the reaction system was cooled to room temperature, 350mL of anhydrous ethanol was added and allowed to stand to obtain a white precipitate. The grafted crude product was filtered and vacuum dried to obtain a grafted crude product. Finally, acetone was used as an organic solvent to perform Soxhlet extraction on the grafted crude product to obtain a refined grafted product. Then 10g zinc sulfate heptahydrate, 5g gluconic acid, 1g benzotriazole, and 100g water were added to stir and dissolve, and the phosphorus-free corrosion and scale inhibitor was obtained by mixing evenly.
[0038] In the present invention, the mixing ratio of the refined graft product and the metal corrosion inhibitor can be selectively mixed by those skilled in the art according to actual needs.
[0039] Comparative test of corrosion inhibition performance of water treatment
[0040] Water from a certain river basin (very low hardness water) was taken as the test water (water quality parameters: pH 6.50, conductivity 97μs / cm, turbidity 2.1mg / L, calcium hardness 8.2mg / L, magnesium hardness 7.0mg / L, total alkalinity 20mg / L, Cl - 19mg / L), refer to "Determination of corrosion inhibition performance of water treatment-rotating hanging plate method"
[0041] (GB / T18175-2014) was used to conduct a rotating hanging plate experiment, and the commercially available low hardness water corrosion inhibitor TH-682 was used as a comparative example to conduct rotating hanging plate experiments with Examples 1-4 (all added at 60 ppm). The specific corrosion inhibition test results are shown in Table 1.
[0042] Table 1 Corrosion inhibition test results of comparative test
[0043]
[0044] It can be seen from Table 1 that under the same addition concentration conditions, the corrosion rates of Examples 1-4 are significantly lower than those of the comparative example. In addition, the corrosion rates of Examples 1-4 are much lower than those specified in the national standard, and the corrosion inhibition effect is excellent. Among them, the national standard GB50050-2017 specifies that the corrosion rate of carbon steel is ≤0.075mm / a, and the corrosion rates of stainless steel and brass are ≤0.005mm / a.
[0045] The above description is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention.
Claims
1. A method for preparing a phosphorus-free corrosion and scale inhibitor for highly corrosive water, characterized in that: The following steps are involved: S1: In an inert gas environment, natural polysaccharides are mixed with distilled water for gelatinization; S2: Cooling the gelatinized system obtained in step S1 to a certain temperature, adding unsaturated monomers, stirring until stable, adding initiator solution, stirring, and performing graft copolymerization reaction; S3: After cooling the reaction system of step S2 to room temperature, anhydrous ethanol is added, and the mixture is allowed to stand, filtered, and dried to obtain a grafted crude product; S4: using an organic solvent to perform Soxhlet extraction on the grafted crude product to obtain a refined grafted product; S5: stirring and dissolving the refined grafted product and the metal corrosion inhibitor aqueous solution, and mixing them evenly.
2. The method for preparing a phosphorus-free corrosion and scale inhibitor for highly corrosive water according to claim 1, characterized in that: In S1, the gelatinization temperature is 70-90° C., and the gelatinization time is 20-60 min.
3. The method for preparing the phosphorus-free corrosion and scale inhibitor for highly corrosive water according to claim 1, characterized in that: In S1, the natural polysaccharide polymer is one or more of starch and chitosan.
4. The method for preparing a phosphorus-free corrosion and scale inhibitor for highly corrosive water according to claim 1, characterized in that: In S2, the gelatinization system is cooled to 40-50°C.
5. The method for preparing a phosphorus-free corrosion and scale inhibitor for highly corrosive water according to claim 1, characterized in that: The mass ratio of the natural polysaccharide to the unsaturated monomer is 1:1-1:
3.
6. The method for preparing the phosphorus-free corrosion and scale inhibitor for highly corrosive water according to claim 1, characterized in that: The added amount of the initiator is 5%-15% of the mass of the unsaturated monomer.
7. The method for preparing the phosphorus-free corrosion and scale inhibitor for highly corrosive water according to claim 1, characterized in that: In S2, the unsaturated monomer is one or more of acrylamide, sodium allyl sulfonate, methyl methacrylate, and methyl acrylate.
8. The method for preparing the phosphorus-free corrosion and scale inhibitor for highly corrosive water according to claim 1, characterized in that: The initiator is sodium persulfate-sodium bisulfite.
9. The method for preparing the phosphorus-free corrosion and scale inhibitor for highly corrosive water according to claim 1, characterized in that: The metal corrosion inhibitor is one or more of zinc salt, gluconic acid and benzotriazole.
Citation Information
Patent Citations
Composite corrosion-inhibiting scale-resisting agent for water with strong corrosion performance
CN1063803C
Environment-friendly metal corrosion inhibitor and preparation method thereof
CN101974762A
Antioxidant corrosion inhibitor
CN110016670A
Corrosion and scale inhibitor for reverse osmosis membranes
CN110201550A
Scale and corrosion inhibitor for industrial circulating cooling water and preparation method of scale and corrosion inhibitor
CN115947465A